Once upon a toad - Frederick, Heather Vogel (Simon & Schuster Books for Young Readers, 2012)
When her mother goes on a NASA mission, Cat Starr is sent to live with her father, stepsister Olivia, and younger brother Geoffrey, but interference by her inept fairy godmother causes toads to appear when Cat speaks and gems to fall from Olivia's mouth, bringing one to the attention of jewel thieves and the other to a secret government laboratory.